P93 Flow restoration in large vessel occlusion is associated with systemic blood pressure reduction. (29th August 2022) - Kyselyova, A; Meyer, L; Sonnenberg, A; Brekenfeld, C; Guerreiro, H; Fiehler, J; Flottmann, F
Abstract : Introduction: Blood pressure management during mechanical recanalization is known to influence the infarct core size and therefore clinical outcome. Aim of study: We investigated the impact of flow restoration on the systemic blood pressure during thrombectomy. Methods: From June 2016 to January 2018 all patients with large vessel occlusion in the anterior circulation undergoing mechanical thrombectomy were screened. Standardized anesthesia protocols were analyzed and systolic, diastolic and mean arterial pressure values throughout the procedure and at the time of the stent retrieval were assessed. Successful recanalization was defined as TICI score≥2b. Patients with treatment under general anesthesia and those with missing data were excluded. Results: Among 253 patients identified, 134 (53%) met the inclusion criteria. Significant reduction of systolic arterial pressure (158mmHg±20mmHg vs. 148mmHg±19mmHg; p<0.001) and mean blood pressure (105mmHg±14mmHg vs. 101mmHg±15mmHg; p<0.001) were seen after thrombectomy maneuver. Successful recanalization was achieved in 117 patients (87%) and was associated with significant reduction of systolic blood pressure values after flow restoration (157mmHg±26mmHg vs. 144mmHg±17mmHg; p=0.009). In 66 cases (49%) no circulation effective medication was applied during the whole procedure. Stent retrieval has led to significant systolic blood pressure drop among these patients (156mmHg±18mmHg vs. 149mmHg±18mmHg; p<0.001) and showed a trend to significant reduction in the group of patients (59, 89%) with successful recanalization (156mmHg±22mmHg vs. 144mmHg±16mmHg; p=0.07). Conclusion: For patients undergoing mechanical recanalization under local anesthesia or conscious sedation flow restoration leads to significant reduction of systolic blood pressure values. Do you have any conflict of interest to declare? : No